Determining the approximate factor VIII level of patients with severe haemophilia A on emicizumab using in vivo global haemostasis assays. Issue 5 (11th June 2021) - Kizilocak, Hande; Marquez‐Casas, Elizabeth; Malvar, Jemily; Carmona, Roxana; Young, Guy
Abstract: Introduction: Emicizumab is a recombinant, humanized bispecific monoclonal antibody that mimics the function of factor VIII (FVIII) which results in a significant reduction in the annualized bleeding rate in patients with haemophilia A (HA), however, the degree with which emicizumab corrects the coagulation defect remains unclear. The objective of this study was to predict the approximate FVIII level in severe haemophilia A patients with inhibitors on emicizumab using global haemostasis assays. Materials and methods: Patients with moderate and mild HA in the non‐bleeding state and healthy controls had FVIII levels and thrombin generation assessed. Linear regression was utilized to model the FVIII levels as a function of the thrombin generation assay parameters and to make a calibration curve of FVIII levels versus peak thrombin and endogenous thrombin potential. Patients with severe haemophilia A with inhibitors on emicizumab had thrombin generation performed in the same manner and their peak thrombin and endogenous thrombin potential results were placed on the calibration curve to calculate their FVIII Equivalency of Emicizumab by Thrombin Generation (F8EmT). Results: All patients with severe HA with inhibitors on emicizumab had F8EmT >10%, suggesting they had been converted to a mild haemophilia phenotype. The patient's weight was inversely correlated to their F8EmT. Conclusion: The results from this study suggest that the F8EmT in patients with severe HA on emicizumab falls within the range of mild haemophilia which is consistent with the data noted in the emicizumab clinical trials and in vivo studies in animals.